Perlawanan dan Pembebasan Kolonialisme pada Tarekat Qadiriyah wa Naqsyabandiyah (1888-1903) - Reni Dian Anggraini (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2020)
This paper explains and describes how tarekat and Sufi political resistance as agents of change and liberation from colonialism in the Qadiriyah wa Naqsyabandiyah order. A Sufi is not a person who only dwells on spirituality, but also with social and political problems, such as resistance and rebellion against colonial rule. In carrying out this resistance, it cannot be separated from the encouragement of the Qadiriyah wa Naqsyabandiyah order. It was the tarekat that played an active role in defending colonialism, which criticized society and the oppression that had been perpetrated by colonialism. In carrying out his defense action, the Sufi order of the Qadiriyah wa Naqsyabandiyah order taught knowledge to his students to fight against colonialism. Fighting colonialism was not easy to go through. It even claimed many lives. Seeing this reality did not diminish the spirit of the tarekat in carrying out their actions as defenders of society in colonialism over colonialism. In this discussion, the authors use the library method by using various related sources in books, journals, and articles. Thus this paper attempts to unravel the problems of Sufism and political resistance and Sufi roles in liberation from colonialism pioneered by the Qadiriyah wa Naqsyabandiyah tarekat. Tulisan ini menjelaskan dan menguraikan tentang bagaimana peran tarekat dalam perlawanan politik, sufi sebagai agen perubahan dan pembebasan dari kolonialisme dalam tarekat Qadiriyah wa Naqsyabandiyah. Seorang sufi bukanlah orang yang hanya berkutat pada spiritualitas, tetapi juga dengan persoalan sosial dan politik, seperti perlawanan dan pemberontakan terhadap penjajahan kolonial. Dalam melakukan perlawanan tersebut tidak bisa terelepas dari dorongan para tarekat Qadiriyah wa Naqsyabandiyah. Tarekatlah yang sangat berperan aktif dalam melakukan pembelaan dari penjajahan kolonialisme yang mengecam masyarakat dan ketertindasan yang telah dilakukan oleh para kolonialisme. Dalam menjalankan asksi pembelaannya, sufi tarekat Qadiriyah wa Naqsyabandiyah mengajarkan ilmu kepada muridnya untuk berjihad melawan penjajahan. Dalam melawan kolonialisme tidak mudah untuk dilalui, bahkan banyak memakan korban jiwa. Melihat realitas tersebut tidak memudarkan semangat para tarekat dalam menjalankan aksinya sebagai pembela masyarakat dalam penjajahan atas kolonialisme. Dalam pembahasan ini penulis menggunakan metode kepustakaan dengan menggunakan berbagai sumber yang terkait berupa buku, jurnal serta artikel. Dengan begitu tulisan ini mencoba untuk menjelaskan bagaimana tasawuf dan perlawanan politik, serta sufi berperan dalam pembebasan dari kolonialisme yang dipelopori oleh tarekat Qadiriyah wa Naqsyabandiyah.